Presenting a Method for Efficient Energy Consumption in Wireless Sensor Networks Using the Topology control and Fuzzy Systems - javedan, Hassan; Shahmohammadi, Gholamreza (International Journal of Computer Sciences and Engineering, 2025)
According to importance the energy consumption in wireless sensor networks, aim of this research is presenting a method to efficient energy consumption in wireless sensor networks. The proposed protocol is based on the basic protocol of topology control with dynamic weight regarding the status of neighbor nodes. Each sensor node has been found its single-stage neighbor, in the first round; it creates graphs and routing using the topology control and only by the distance parameter. In the next periods, regarding the differences in the residual energy of nodes and their load traffic in the previous round, using the fuzzy inference system and applied fuzzy rules and by applying the parameters of residual energy, traffic load and distance, will be performed for selection the connectivity node. The proposed idea is that the degree of any node is not more than 4. One advantage of an efficient protocol in topology management is having the number of optimal neighbor. As the number of connected neighboring nodes is less and more optimized, work efficiency is higher. Due to balancing the energy consumption in all network nodes, the network lifetime, which is the most important concern of wireless sensor networks, is increased. Simulation results show that the proposed algorithm compared with baseline algorithms has better efficiency and performance.